(untitled) (Scientific journal of the Fergana State University, 2024)
This article highlights the analysis of the results obtained from an experiment aimed at increasing the general physical fitness of young football players. Pedagogical experience in terms of physical fitness indicators of 15-year-old football players of the control and experimental groups on test tests selected based on the analysis of available scientific and methodological literature materials and data from our personal practical experience among authentic tests. characterizing indicators of physical fitness of athletes.